PENGGUNAAN KOTORAN AYAM DAN PUPUK UREA UNTUK PEMBIBITAN TANAMAN KETAPANG (Terminalia catappa. L.) PADA MEDIA PASIR TAILING - Nursiah, Nursiah; Muin, Abdurrani; Burhanuddin, Burhanuddin (JURNAL HUTAN LESTARI, 2020)
In general, the fertility rate of ex-mining tailings sand is very low, so plants to restore it must be fertilized with the right type and dosage. One type of plant that can be used for ex-mining land (tailings) is the Ketapang plant (Terminalia catappa L). The research objectives determine (1) the effect of the use of chicken manure fertilizer and urea dose on the growth of ketapang seedlings in the nursery and (2) the composition of chicken manure fertilizer with tailings and the dose of urea fertilizer for the growth of ketapang seedlings in the nursery. This research was carried out in Ketapang City by factorial completely randomized factorial design (RAL) method. The experimental treatment consisted of giving chicken manure and urea fertilizer to the tailings media. The first factor is chicken manure (T) tailing media without sand chicken manure (T0), 1: 1 (T1), 1: 2 (T2), and 1: 3 (T3). The second factor is the addition of urea fertilizer with a dose of 0 grams (P0), 0.5 g (P1), 1.0 g (P2), 1.5 (P3), and 2 g (P4). Each treatment combination was repeated 3 times so that in the experiment as many as 60 seeds were used. Data collected in the form of seedling height (cm), base diameter (mm), number of leaves (strands), and dry weight of seeds (g). The results showed that the treatment of chicken manure and urea fertilizer on ketapang seedlings on the tailings sand media in the nursery significantly affected the diameter and biomass growth (dry weight) of ketapang plant seeds (T. catappa L). The use of chicken manure fertilizer without urea fertilizer could increase height growth and the number of leaves. The composition by comparing one part of tailings sand with one, two, and three parts of chicken manure does not show a significantly different effect. This means that for the nursery of ketapang plants, it is sufficient to use the composition of one part tailing sand and one part chicken manure. Giving urea fertilizer without chicken manure has not been able to improve the growth of ketapang seedlings (T. catappa L).Keywords: chicken manure, ketapang plants, tailings Sand, urea fertilizer